Recent development and application of cyclometalated iridium(iii) complexes as chemical and biological probes. Issue 19 (26th April 2021) - Shi, Hongdong; Wang, Yi; Lin, Simin; Lou, Jingxue; Zhang, Qianling
Abstract : The recent development and application of iridium-based probes for sensing ions, anions, gaseous species, organic molecules, small biomolecules, biomacromolecules, and subcellular organelles are highlighted in this review. Abstract : Iridium complexes have been widely applied as molecular sensors because of their rich photophysical properties, including large Stokes shifts, long emission lifetimes, environment-sensitive emissions, and high luminescence quantum yields. In this paper, we review the recent development and application of iridium complexes as probes for ions, anions, gaseous species, organic molecules, small biomolecules, biomacromolecules, and subcellular organelles. Our outlook for iridium-based probes is also discussed.